Digestive and bacterial enzyme activities in broilers fed diets supplemented with Lactobacillus cultures - Jin, L.Z.; Ho, Y.W.; Abdullah, N.; Jalaludin, S. (Elsevier, 2000)
A study was carried out to investigate the effects of adherent Lactobacillus cultures on 1) amylolytic, lipolytic, and proteolytic enzyme activities in the contents of the small intestine (from the distal end of the duodenum to the ileocecal junction) and 2) bacterial β-glucuronidase and β-glucosidase activities in the intestinal contents and feces of broiler chickens. Three dietary treatments were randomly assigned to three groups of chicks, i.e., basal diet only (control group), basal diet + 0.1% dried culture of Lactobacillus acidophilus, and basal diet + 0.1% dried culture of a mixture of 12 Lactobacillus strains. The results showed that supplementation of the adherent Lactobacillus cultures to chickens, either as a single strain of L. acidophilus or as a mixture of 12 Lactobacillus strains, increased significantly (P < 0.05) the levels of amylase in the small intestine. However, the proteolytic and lipolytic activities in the small intestine were not affected by addition of either of the adherent Lactobacillus cultures. Addition of either L. acidophilus or a mixture of 12 Lactobacillus strains was also found to reduce significantly (P < 0.05) the intestinal and fecal β-glucuronidase and fecal β-glucosidase but not the intestinal β-glucosidase at 40 d of feeding.